Sjögren’s Syndrome without focal lymphocytic infiltration of the salivary glands - Sharma, Rohan (J Rheumatol, 2019)
BACKGROUND. Primary Sjögren’s syndrome (SS) is characterized by a focal lymphocytic infiltrate in exocrine glands. We undertook this study to describe patients that lacked this key feature. METHODS. We evaluated subjects with sicca in a comprehensive clinic at which medical, dental and ophthalmological examinations were performed. All subjects underwent a minor salivary gland biopsy with focus score calculation. Extra-glandular manifestations were also determined. We categorized subjects as high, intermediate, or low in terms of the expression of interferon-regulated genes. RESULTS. About 20% (51 of 229, 22%) of those classified as primary Sjögren’s syndrome had a focus score of zero. Compared to those with anti-Ro positivity and a focus score >1.0, the focus score zero patients (who by classification criteria must be anti-Ro positive) were statistically less likely to have anti-La (or SSB) and elevated immunoglobulin as well as less severe corneal staining. In addition, the focus score zero patients were less likely to have elevated expression of interferon-regulated genes in peripheral blood mononuclear cells than anti-Ro positive SS subjects with a focal salivary infiltrate. CONCLUSIONS. There are only a few clinical differences between primary Sjögren’s syndrome patients with focus score zero and those with both anti-Ro and a focus score >1.0. Nonetheless, the small subset of focus score zero patients tested did not have elevated expression of interferon-regulated genes, but did have systemic disease. Thus, extra-glandular manifestations are perhaps more related to the presence of anti-Ro than increased interferon. This may have relevance to Sjögren’s syndrome pathogenesis.